ECOLINGUISTIC ANALYSIS OF ENVIRONMENTAL ISSUES IN THE INDONESIAN RELIGIOUS LEADER’S SPEECH - Nuriel Shiami Indiraphasa; Afrillia Firmonasari (CALL, 2026)
This study examines how environmental responsibility is discursively constructed in Alissa Qotrunnada Wahid’s speech by situating it within broader debates on religion, language, and the global climate crisis. The research aims to identify the ideological orientation of the speech and to evaluate its ecological implications through critical discourse analysis. Employing Fairclough’s (2003) three-dimensional model, textual analysis, discursive practice, and social practice, this study is complemented by Halliday’s transitivity system as well as the ecolinguistics and ecosophy framework developed by Stibbe (2021). The findings reveal that, at the textual level, the speech is dominated by material, relational, and mental processes, which collectively construct environmental protection as concrete, urgent, and morally grounded collective action rather than a purely abstract or normative appeal. The inclusive pronoun “we” positions religious institutions and communities as active agents of change, while relational processes establish environmental protection as an essential ethical and spiritual value. At the level of discursive practice, the speech is produced and legitimized through the symbolic authority of major religious organizations, particularly Nahdlatul Ulama and the GUSDURian Network, and disseminated through both formal education and grassroots community-based initiatives, including interfaith and family-centered programs. In the dimension of social practice, the discourse reflects and responds to Indonesia’s ecological challenges and advances religious ideology that frames nature as a moral trust integral to religious teachings. From an ecolinguistic perspective, the analysis concludes that the speech predominantly constitutes a beneficial discourse. It affirms values of sustainability, rejects exploitative representations of nature, and actively promotes the transformation of awareness and collective social practice toward ecological responsibility.